2013
DOI: 10.1159/000351438
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Mortality in Patients Undergoing Transcatheter Aortic Valve Implantation: Comparison of the Novel EuroScore II with Established Risk Scores

Abstract: Objectives: In the evaluation of patients considered for transcatheter aortic valve implantation (TAVI), the EuroScore II might be superior to established risk scores. Methods: We assessed the performance of the EuroScore II in predicting mortality in a cohort of 350 TAVI patients. Results: The EuroScore II and the logistic EuroScore were higher in nonsurvivors compared to survivors at 30 days (12.6 ± 1.8 vs. 7.5 ± 0.3%, p < 0.001 for EuroScore II, and 27.7 ± 2.8 vs. 22.1 ± 0.8%, p = 0.04 for logistic EuroScor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 33 publications
1
27
1
2
Order By: Relevance
“…Despite that, in our study, STS score did not prove to be better able to predict mortality. 16 A finding in this study was that the left ventricular ejection fraction of patients who progressed to death was significantly higher than seen in the survivors (65.25±1.74% for death and 54.58±14.18 for survival; p=0.03). However, the average of the two groups was within the normal range and none of the witnessed deaths was due to cardiogenic shock.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…Despite that, in our study, STS score did not prove to be better able to predict mortality. 16 A finding in this study was that the left ventricular ejection fraction of patients who progressed to death was significantly higher than seen in the survivors (65.25±1.74% for death and 54.58±14.18 for survival; p=0.03). However, the average of the two groups was within the normal range and none of the witnessed deaths was due to cardiogenic shock.…”
Section: Discussionmentioning
confidence: 46%
“…While Stahli et al 16 in a cohort of 350 patients and Sedaghat et al 15 in a cohort of 206 patients demonstrated the superiority of EuroSCORE II, Hemmann et al 17 in a record of 426 patients considered the STS superior. Other studies, as well as our work, demonstrated no difference between the scores, and, in our case, both the EuroSCORE II and STS scores had the ability to predict mortality, with AUC of 0.77 and 0.81, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the whole patient cohort, all-cause mortality was 9.1% at 30 days [18]. Causes of death at 30 days were cardiovascular in 96.8% (31 of 32) of patients.…”
Section: Varc-2 Composite Endpoints: Device Success and Early Safetymentioning
confidence: 92%
“…Recently several studies have focused their attention on the large proportion of AS population defined at intermediate-risk (STS risk score between 4% and 8%) and at low-risk (STS risk score < 4%) [26,27] . Under current guidelines, the choice to perform TAVI for that group of patients should be allowed only after a specific cases selection by the Heart Team and, importantly, in centers with well-established procedural training.…”
Section: Intermediate and Low Risk Patientsmentioning
confidence: 99%